A model for genomic imprinting in the social brain: elders. - Úbeda, F; Gardner, A (2012)
Genomic imprinting refers to the process whereby genes are silenced when inherited via sperm or egg. The most widely accepted theory for the evolution of genomic imprinting-the kinship theory-argues that conflict between maternally inherited and paternally inherited genes over phenotypes with asymmetric effects on matrilineal and patrilineal kin results in self-imposed silencing of one of the copies. This theory was originally developed in the context of fitness interactions within nuclear families, to understand intragenomic conflict in the embryo and infant, but it has recently been extended to encompass interactions within wider social groups, to understand intragenomic conflict over the social behavior of juveniles and adults. Here, we complete our model of genomic imprinting in the social brain by considering age-specific levels of expression in a society were generations overlap, to determine how intragenomic conflict plays out in older age. We determine the role of sex bias in juvenile dispersal, reproductive success, and adult mortality in mediating the direction and intensity of conflict over the competing demands of parental and communal care as the individual ages. We discover that sex-specific asymmetries in these demographic parameters result in intragenomic conflict at early age but this conflict gradually decays with age. Although individuals are riven by internal conflict in their youth and middle age, they put their demons to rest in later life.